Did the Hospital Readmissions Reduction Program Reduce Readmissions without Hurting Patient Outcomes at High Dual-Proportion Hospitals Prior to Stratification?. (12th December 2022) - Yang, Zhiyou; Huckfeldt, Peter; Escarce, Jose J.; Sood, Neeraj; Nuckols, Teryl; Popescu, Ioana
Since the implementation of Medicare's Hospital Readmissions Reduction Program (HRRP), safety-net hospitals have received a disproportionate share of financial penalties for excess readmissions, raising concerns about the fairness of the policy. In response, the HRRP now stratifies hospitals into five quintiles by low-income Medicare (dual Medicare–Medicaid eligible) stay proportion and compares readmission rates within quintiles. To better understand the potential effects of the revised policy, we used difference-in-differences models to compare changes in 30-day readmission, 30-day mortality, and 90th-day community-dwelling rates after discharge of fee-for-service Medicare beneficiaries hospitalized for acute myocardial infarction, heart failure and pneumonia during 2007-2014, for hospitals in the highest ( N = 677) and lowest ( N = 678) dual-proportion quintiles before and after the original HRRP implementation in fiscal year 2013. We find that high dual-proportion hospitals lowered readmissions for all three conditions, while their patients' health outcomes remained largely stable. We also find that for heart failure, high dual-proportion hospitals reduced readmissions more than low dual-proportion hospitals, albeit with a relative increase in mortality. Contrary to concerns about fairness, our findings imply that, under the original HRRP, high dual-proportion hospitals improved readmissions performance generally without adverse effects on patients' health. Whether these gains could be retained under the new policy should be closely monitored.